Charakterystyka systemów informowania kierownictwa - Sitarska, Monika (Executive Information Systems (EIS) Characteristics, 2007)
The main subject of current paper is an attempt to systematize the knowledge about Executive Information Systems (EIS). They are the important applications supporting decision processes of top managers. The article describes the following EIS: definitions, functions, structure and used information technology.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (11); 2007; nr 1156, s. 68-75